Open Access policies and experiences in Norway, Romania and Moldova - Landoy, Ane; Ghinculov, Silvia; Repanovici, Angela; Cheradi, Natalia (Qualitative and Quantitative Methods in Libraries, 2017)
The paper looks at Open Access strategies and resources that promote a new paradigm of scientific communication and provide benefits to science and society. It analyzes the documents that institutionalize Open Access within the University of Bergen, the Transilvania University of Brasov and the Academy of Economic Studies of Moldova. Implementing Open Access within the Moldovan-Romanian-Norwegian collaboration will improve dissemination of scientific knowledge in a spirit promoted by international initiatives and declarations. There is a need for increased responsiveness to changes that occur in all spheres of life, particularly in the field of information and communication. Under these circumstances, the role of the library in promoting scientific knowledge through various ways and methods increases enormously. The access to information and information sharing is essential for the successful development of society, and librarians play a crucial role in the promotion of Open Access to digital scientific information.